Contextual Study of Religious Moderation Values in Islamic Education for Multicultural Social Behavior in the Sukra Village Community - Rofik Hijazi (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze the implementation of religious moderation values in Islamic education and their contribution to shaping the multicultural social behavior of the community in Sukra Village, Sukra District, Indramayu Regency. Sukra Village is an area with a relatively high level of social heterogeneity in terms of culture, ethnicity, and religion. The research employs a qualitative-descriptive approach, with data collected through observation, in-depth interviews, and documentation. The findings indicate that the internalization of religious moderation values such as tawasuth (moderation), tasamuh (tolerance), tawazun (balance), and ta’adul (justice) has been implemented in various formal and non-formal Islamic educational activities, including religious study gatherings, family education, and the roles of religious leaders. This implementation has had a significant impact on strengthening attitudes of tolerance, willingness to deliberate, and rejection of extreme religious ideologies within the community. Supporting factors for the implementation of religious moderation include the role of religious leaders, educational institutions, and the community’s open social culture. Meanwhile, the inhibiting factors include the influence of social media, limited digital literacy, and the presence of certain exclusive groups. This study recommends strategies for strengthening religious moderation through contextual, collaborative Islamic education models based on local wisdom values.